Preface - CTA Editorial Board (Chimica Techno Acta)
This issue is dedicated to Professor Alexander Petrov, whose 75th birthday we have celebrated this year. During all his life Alexander Petrov was deeply involved into teaching and research in the Chemical Faculty of the Ural State University. His research interests included wide range of topics concerning thermodynamics and stability of oxide systems, crystal and defect structure, charge and mass transfer, technical applications of oxide materials, and many others. Professor Petrov is a co-author of many publications, patents, and text-books. Together with his teacher, Professor Vladimir Zhukovsky, Alexander Petrov became a founder of outstanding research group for Solid State Chemistry in the Ural State University, which raised many talented young scientists. He was one of the first scientists of the Ural State University who managed to go on an internship abroad, to Professor P. Kofstad. As a result, since mid-70th, Oslo University remains our good partner for collaboration in different forms. Later, Professor Petrov took part in research in well-known research centers in Italy, Denmark, USA, and many others, and delivered lectures at international conferences as an invited speaker. For 22 years (1986-2008) Professor Petrov headed the Department of Physical Chemistry in the Ural State University. During that time, he made a lot of effort to maintain close collaboration with Institutes of Ural Branch of the Russian Academy of Science and its predecessor - the Academy of Science of the USSR. In 1987, he organized a joint laboratory with the Institute of Electrophysics. A branch of the Department of Physical Chemistry was established in 1995 in the Institute of High-Temperature Electrochemistry. A scientific laboratory “Neutron-diffraction studies of complex oxides” was organized jointly with the Institute for Metal Physics in 1997. It can be said that Professor Petrov anticipated the trends that the Ministry of Science and Higher Education of Russia is currently implementing. Alexander Petrov repeatedly won high awards. For example, in 1989 together with others he was awarded by the Prize of the Council of Ministers of the USSR for the development of novel ceramic cathodes for CO2-lasers, in 2000 he was awarded the State Scholarship for Outstanding Scholars of the Russian Federation, in 2001 he was awarded the Honored Scientist of the Russian Federation title. In addition to his merits and titles, the most important traits of Alexander Petrov were his outstanding humanity and decency. He was always ready to fight for justice and come to the rescue. More than 10 years have passed since he is not with us, but we still keep bright memories and warm feelings towards him in our hearts.